Effect of Acute Hypercapnia on Outcomes and Predictive Risk Factors for Complications among Patients Receiving Bronchoscopic Interventions under General Anesthesia - Cheng, Qinghao; Zhang, Jieli; Wang, Hongwu; Zhang, Rujin; Yue, Yun; Li, Lei (PLOS ONE, 2015)
Background The aim of this study is to investigate the effect of acute hypercapnia on surgery outcomes among patients receiving bronchoscopic interventions under general anesthesia. Furthermore, independent predictive factors for surgery complications were analyzed. Method A total of 323 patients with airway stenosis were enrolled in this retrospective study. Each patient underwent interventional rigid bronchoscopy under general anesthesia. Arterial blood gas (ABG) was measured intraoperatively. In light of PaCO2 levels in ABG, patients were divided into three groups: Group C (control) (PaCO2:≤ 60 mmHg), Group M (moderate) (PaCO2:61–100 mmHg), and Group S (severe) (PaCO2: >100 mmHg). Parameters, including PaO2 levels and recovery delays, were compared across three groups. Complications among patients receiving bronchoscopic interventions were evaluated as well. Independent predictive factors for surgery related complications were analyzed by multivariable regression method. Results Significant differences in weight (p=0.04), ASA IV (p=0.008), dyspnea index (p=0.003),COPD (p=0.02), dynamic airway collapse (p=0.002), severe stenosis severity (p=0.02), and stenosis locations among three groups were observed. Mild (PaCO2: 60 mmHg) to moderate (PaCO2:60–100 mmHg) hypercapnia was not associated with delayed recovery, whereas severe hypercapnia (PaCO2:>100 mmHg) was associated with delayed recovery, as well as declined PaO2 (p=0.00) and elevated blood glucose levels (p=0.00). The complications of bronchoscopic interventions included postoperative congestive heart failure (14 cases, 4.3%), tracheorrhagia (8 cases, 2.5%), delayed recovery (19 cases, 5.9%), and transfers to ICU after surgery (10 cases, 3.1%). The multivariable regression analysis showed that procedure duration (p=0.003), lobectomy (p=0.007), dynamic airway collapse (p=0.01), severe bronchial stenosis (p=0.01) and hypercapnia (p=0.02) were independent predictive factors for surgery related complications. Conclusions Acute hypercapnia lower than 100 mmHg was not associated with detrimental consequences, whereas severe hypercapnia (PaCO2: >100 mmHg) was associated with lower levels of PaO2. Hypercapnia was an independent predictive factor for bronchoscopic intervention complication, which may help physicians to optimize the therapeutic choices.